Nomenclatural notes on Cyornis and Rhinomyias flycatchers (Aves: Muscicapidae) of South-East Asia - Mlíkovský, Jiří (Zootaxa, 2011)
A nomenclatural revision of two flycatcher names first introduced into the literature by Blyth (1870) and other relevant names showed the following: (1) Cyornis cyanopolia should be attributed to Blyth (1870) and is a valid name for the flycatcher Cyornis unicolor cyanopolia Blyth. (2) Muscicapa infuscata should be attributed to Blyth (1870) and is a junior subjective synonym of Rhinomyias umbratilis (Strickland, 1849). (3) Cyornis infuscata Hartert, 1902, never existed as a zoological name. (4) Cyornis harterti Robinson & Kinnear, 1928, is not available for nomenclatural purposes.